Answer:
A. 6
Step-by-step explanation:
f(x) = x² − 12x + 7
To complete the square, we first factor the leading coefficient to make it 1 (which it already is).
Then, we take half the second coefficient, square it, and then add to both sides. So (-12/2)² = (-6)² = 36.
f(x) + 36 = x² − 12x + 36 + 7
Then we factor the perfect square:
f(x) + 36 = (x − 6)² + 7
Then solve for f(x) by subtracting and simplifying:
f(x) = (x − 6)² + 7 − 36
f(x) = (x − 6)² − 29
So the value of a is 6.
Answer:
A) 60
Step-by-step explanation:
P = 5+5+11+9+(5+11)+(9+5)
P = 60
Answer:
it's C ;)) maybe i guess-
Step-by-step explanation:
Answer:
c
Step-by-step explanation:
-7.5 is less than 6.5
Answer:
n = 13
Step-by-step explanation:
24 = 3 (n-5)
3n - 15 = 24
3n = 24 +15
3n = 39
n = 39/3
n = 13